Solve this system of equations. x + xy + y = 11 (x^2)(y) + x(y^2) = 30
x + xy + y = 11............eq.1 (x^2)(y) + x(y^2) = 30..........eq.2 xy + y = 11-x.............1) (x +1) y = 11-x y = (11-x)/(x +1)..........substitute in (x^2)(y) + x(y^2) = 30.............eq.2 (x^2)((11-x)/(x +1)) + x((11-x)/(x +1))^2 = 30 (x (11 - x) (x^2 + 11))/(x + 1)^2 = 30 x (11 - x) (x^2 + 11)= 30(x + 1)^2 x (11 - x) (x^2 + 11)= 30(x + 1)^2 -x^4 + 11 x^3 - 11 x^2 + 121 x=30 x^2 + 60 x + 30 -x^4 + 11 x^3 - 41 x^2 + 61 x - 30 = 0..........using calculator we get x=1, x=2, x=3, x=5 then y = (11-x)/(x +1)=(11-1)/(1 +1)=10/2=5 y = (11-x)/(x +1)=(11-2)/(2 +1)=9/3=3 y = (11-x)/(x +1)=(11-3)/(3 +1)=8/4=2 y = (11-x)/(x +1)=(11-5)/(5 +1)=6/6=1 solutions: x=1, y=5 x=2, y=3 x=3, y=2 x=5, y=1
Thank you very much. No more monster questions. We will go back to our College Algebra textbook when time allows and when the heatwave goes away. I am moving to my new place on August 7.